Two Worlds Colliding: The Interplay Between Natural Compounds and Non-Coding Transcripts in Cancer Therapy - Sabo, Alexandru A.; Dudau, Maria; Constantin, George L.; Pop, Tudor C.; Geilfus, Christoph-M.; Naccarati, Alessio; Dragomir, Mihnea P. (Frontiers in Pharmacology, 2021)
Cancer is a devastating disease and has recently become the leading cause of death in western countries, representing an immense public health burden. When it comes to cancer treatment, chemotherapy is one of the main pillars, especially for advanced stage tumors. Over the years, natural compounds have emerged as one of the most valuable resources for new chemotherapies. It is estimated that more than half of the currently used chemotherapeutic agents are derived from natural compounds. Usually, natural compounds are discovered empirically and an important limitation of introducing new anti-cancer natural products is not fully understanding their mechanism of action. Recent data has proven that several natural compounds may function via modulating the expression and function of non-coding RNAs (ncRNAs). NcRNAs are a heterogenous class of RNA molecules which are usually not translated into proteins but have an important role in gene expression regulation and are involved in multiple tumorigenic processes, including response/resistance to pharmacotherapy. In this review, we will discuss how natural compounds function via ncRNAs and summarize the available data on several types of cancers. Moreover, we will critically analyze the current advances and limits in understanding the function of natural compounds via ncRNAs. Finally, we will propose several new hypotheses that could open new perspective regarding the interaction between natural compounds and ncRNAs and that could lead to better natural compound-based therapeutic strategies in cancer.